TUGAS PRAKTIKUM KELOMPOK (TPK) FISIKA SEBAGAI ALAT EVALUASI PEMBELAJARAN FISIKA DENGAN MENGGUNAKAN LKS COMPETENCE BASED PROCESS SKILLS - Wenno, I.H. (PROSIDING : Seminar Nasional Fisika dan Pendidikan Fisika, 2012)
The aim of learning and teaching process are depends on involve betwen teacher and student and fasility that are same with combined in material was learned. In the physics learning, it is usually used by TPK with eksperimental method there is a skill process approach used by teacher to increase the student learning result. The TPK are purposeses to make the student exercise learn in groups, and make teacher easy to look for personal student ability. To evaluate stutent ability, the method used are discriftif method applied with LKS (Student Work Sheet) is prepared by researcher and all laboratory equipments, than students try to arrange the eksperimental design according to the instructions.This research found that all of laerning result of students are 85 %. It means that TPK as an evaluation instrument of skill process approach developed by teacher, can be optimalisation as an intruments of student learning assesment. Finally, this research conclude that student skill process can be increase rapidly in the short time of all learning process. Key Words : Groups practically task, Skill Process Approach, Physics Learning In School.